Exploring positive adjustment in people with spinal cord injury. (August 2014) - Dibb, Bridget; Ellis-Hill, Caroline; Donovan-Hall, Margaret; Burridge, Jane; Rushton, David
This study explored adjustment in people with spinal cord injury; data from four focus groups are presented. Thematic analysis revealed four themes, managing goals and expectations, comparison with others, feeling useful and acceptance, showing participants positively engaged in life, positively interpreted social comparison information and set realistic goals and expectations. These positive strategies show support for adjustment theories, such as the Cognitive Adaptation Theory, the Control Process Theory and Response Shift Theory. These results also provide insight into the adjustment process of a person with spinal cord injury and may be useful in tailoring support during rehabilitation.